Ritual Slaughter: The Tradition of Pilot Whale Hunting on the Faroe Islands - Mamzer, Hanna Maria (Frontiers in Veterinary Science, 2021)
Faroese people consider grindadráp, the hunting of pilot whales, as a part of their cultural heritage, but from the point of view of veterinary sciences and biology, the method of killing pilot whales is a form of a ritual slaughter performed on fully conscious animals that are aware of their circumstances. Pilot whales are social, intelligent, and communicative animals that demonstrate complex social behaviors. Therefore, this traditional whaling method should be considered as a procedure in which animals are exposed to high levels of distress. In the context of contemporary civilizational development and material welfare, the practice of whaling may appear to be an inadequate and cruel relic of the past. This text explores social and cultural issues caused by pilot whale hunts and presents an understanding of the term tradition and some perspectives of how traditions change. The specificity of pilot whales as a species is presented, setting a foundation for a discussion about hunting itself. The conclusion of the text discusses different social perceptions of grindadráp by presenting arguments for and against the hunting. This analysis includes a presentation of actions undertaken bywhale hunting opponents.